Establishing the Nexus between Climate Change, Force Migration and Food Production/Security in Nigeria: Research Observations of Historian and Agriculturist - Emmanuel Osewe AKUBOR; Beatrice Amili AKUBOR (UIN Sunan Gunung Djati, 2021)
This research tries to interrogate the readiness of Third World countries for the challenges facing climate change, the consequences of this climate change will affect more than 200 million people which make fish resources severely reduced and other species migrate which makes inhabitant even more miserable. Coastal communities can also be displaced by rising sea levels and will be forced to find new housing and new livelihoods. This will pose new risks to food security, food security and human health. using a qualitative approach and historical research methods to find past experiences to solve this problem. This research results that most of the damage to the ecosystem is done by humans to survive without paying attention to environmental factors and we also find history. Experts have realized the importance of forests as an antidote to climate change, but the implementation in the field of protection is still lacking.